TWEETING @THEWRITERSROOM: MAPPING THE TELEVISION INDUSTRY’S IDEAL FAN THROUGH WRITERS’ ROOM TWITTER ACCOUNTS - Navar-Gill, Annemarie (AoIR Selected Papers of Internet Research, 2015)
In the current television environment, it has become particularly important for the industry to become involved in audience social media practices. Evans (2014) argues that audience conversations on social media become part of the program and network’s brand. Given the number of voices involved in these conversations, it is essentially impossible for the network to manage its brand(s) as effectively as desired. Engaging in social media with fans provides a way to steer audience social media behaviors in favorable directions, and reward “good” fans by highlighting their comments. This study investigates a recent television social media trend: the increasingly popular practice of a show’s writing staff engaging with fans collectively via a writers’ room Twitter account. I engage in analytics-supported qualitative analysis of a sample of tweets from writers’ room Twitter accounts, tracking patterns of interaction and non-interaction with fans who tweeted to the writers as well as conducting textual analysis of the Tweets in order to identify the strategies being used to manage fan participation and hail particular fan identities. Though all of the writers’ room Twitter accounts that I examined selectively engaged with fans in ways that hail a fan identity that labors for and promotes industrial interests, they do so by invoking a variety of different strategies ranging from crass promotion to fostering personal intimacy. Through the lens of writers’ room Twitter accounts, this project identifies a number of different ways that the television industry is using Twitter to manage its audiences.